The human record - Andrea, Alfred J (Wadsworth Cengage Learning, 2012)
Includes bibliographical references.; v. 1. To 1500 -- v. 2. Since 1500.; v. 2. Since 1500. Prologue: Primary sources and how to read them -- Part 1: An era of change and increased global interaction : the fifteenth through seventeenth centuries. Europe in an age of conflict and expansion ; The Islamic heartland and India ; Africa and the Americas ; Continuity and change in East and Southeast Asia -- Part 2: An era of transition and transformation : the world from the mid-seventeenth to the early nineteenth century. Europe and the Americas in the age of science, economic growth, and revolution ; Africa, Southwest Asia, and India in the seventeenth and eighteenth centuries ; Change and continuity in East Asia -- Part 3: The world in the age of western dominance : 1800-1914. The west in the age of industrialization and imperialism ; Western pressures, nationalism, and reform in Africa, Southwest Asia, and India in the 1800s ; East and Southeast Asia confront the west -- Part 4: The global community and its challenges in the twentieth and twenty-first centuries. The western world in crisis ; Anticolonialism, nationalism, and revolution in Africa, Asia, and Latin America ; The global community from the 1940s through the 1980s ; The world since 1990.